Демократизація та насильство в Бразилії: суперечливі взаємовідносини моралі та політики - Ткач, О.; Ткач, А. (Київський національний університет імені Тараса Шевченка, 2018)
В статті розглядаються особливості насильства в політиці, яке для Бразилії є проблемою політичної системи. Насильство пронизує всі рівні державного управління (федеральний, регіональний, муніципальний) і всі гілки влади. Незважаючи на заходи, прийняті на державному рівні, проблема як і раніше залишається актуальною. Служби контролю розгалужуються, але при цьому не стають ефективними. Неформальні практики суспільних взаємин, що є важливою частиною бразильської політичної культури, також впливають на ефективність боротьби з насильством: в Бразилії викликана недосконалістю інститутів. Методологія статті містить системні, структурно-функціональні, порівняльно-політичний підходи, методи аналізу, синтезу, індукції, дедукції, спостереження, моделювання. У даній статті проаналізована природа насильства "по-бразильски" та її особливості, заходи для боротьби з нею на всіх рівнях державного управління, досягнуті результати і нові виклики.

The article analyzes the priorities the processes of humanization of politics through the concept of non-violence are investigated; the advantages of the evolutionary-reforming way of the social-political development as compared with the revolutionary-violent one and the inadmissibility of political violence leading to the dehumanization of social relations, material and human losses are well grounded. Humanistic ideas of M. Gandy, M.-L. King and the importance and historical experience of their realization are presented. Their actualization in political practice in Ukraine and in modern international relations is shown. The interrelations of morals and politics, the role of morals in reforming politics, the correlation of general and corporate levels of morals are investigated. Non-violence is shown to be the moral principle of politics, the implementation of which provides social and historical succession. Political violence as the states possess a monopoly on using force, they must react on the acts of political violence, accomplished by the not states, and separate persons or groups, especially when such actions suppose using force. Aims of such actions can be two kinds: To prang the existent social and political system with view of to replace her other. The political violence legally shown in a political crime must be determined on two basic elements: Reason of action must be political, i.e. to pursue one of the aims indicated higher. This reason distinguishes political violence from ordinary crimes. A like action can be considered as an ordinary or political crime depending on his reason. Subject of violence can be only a person or separate group of persons (organization, party). The real origin of political violence renders the different affecting potential of future violence, changing depending on the degree of success of dissidents and types of answer of the mode on him. The third type of theories binds violence to the dynamics of conflict. There are competitive groups in any society – economic, political, spiritual. Beginning of competition of groups and personalities – it potential. Reasons of economic inequality in Brazil became cause for violence. D. Gerring defined that than longer a country is democratic, so much the better economically developed she is. On the example of Brazil see that she became on the way of democratic development not so a long ago – in 80th XX of century, but already has one of the most powerful economies of the world. It can be explained by other conception, offer А. Pshevorsкy, that in the states in that GDP makes less than 3 thousand dol. per capita, mode not important for efficiency or unefficiency of development of country, then, as in the states, where GDP per capita over 3 thousand дол., democracy is kept and develops better. Key words: Brazil, non-violence, humanism, morals, spirituality, politics, moral politics, policy of non-violence, humanization of politics, humane objectives, social justice, common for all people values, consensus.
Democracy and violence in Brazil
Keywords: Бразилія; насильство; демократія; політичні інститути; законодавство; безпека; Brazil; non-violence; humanism; morals; spirituality; politics; moral politics; policy of non-violence; humanization of politics; humane objectives; social justice; common for all people values; consensus